First extensive characterization of the venom gland from an egg parasitoid: structure, transcriptome and functional role. (May 2018) - Cusumano, Antonino; Duvic, Bernard; Jouan, Véronique; Ravallec, Marc; Legeai, Fabrice; Peri, Ezio; Colazza, Stefano; Volkoff, Anne-Nathalie
Graphical abstract: Highlights: First extensive characterization of the venom gland of an egg parasitoid resolved. The venom induces a melanized-like process in host eggs. The venom also impairs larval development of another egg parasitoid species. The most abundantly transcribed sequences in the venom gland are discussed. Abstract: The venom gland is a ubiquitous organ in Hymenoptera. In insect parasitoids, the venom gland has been shown to have multiple functions including regulation of host immune response, host paralysis, host castration and developmental alteration. However, the role played by the venom gland has been mainly studied in parasitoids developing in larval or pupal hosts while little is known for parasitoids developing in insect eggs. We conducted the first extensive characterization of the venom of the endoparasitoid Ooencyrtus telenomicida (Vassiliev), a species that develops in eggs of the stink bug Nezara viridula (L.). In particular we investigated the structure of the venom apparatus, its functional role and conducted a transcriptomic analysis of the venom gland. We found that injection of O. telenomicida venom induces: 1) a melanized-like process in N. viridula host eggs (host-parasitoid interaction), 2) impairment of the larval development of the competitor Trissolcus basalis (Wollaston) (parasitoid-parasitoid interaction). The O. telenomicida venom gland transcriptome reveals a majority of digestive enzymes (peptidases and glycosylases) and oxidoreductases (laccases) among the most expressed genes. The former enzymes are likely to be involved in degradation of the host resources for the specific benefit of the O. telenomicida offspring. In turn, alteration of host resources caused by these enzymes may negatively affect the larval development of the competitor T. basalis . We hypothesize that the melanization process induced by venom injection could be related to the presence of laccases, which are multicopper oxidases that belong to the phenoloxidases group. This work contributed to a better understanding of the venom in insect parasitoids and allowed to identify candidate genes whose functional role can be investigated in future studies.